Genetic Stabilization of the Drug-Resistant PMEN1 Pneumococcus Lineage by Its Distinctive DpnIII Restriction-Modification System - Rory A. Eutsey (American Society for Microbiology, 2015)
ABSTRACT The human pathogen Streptococcus pneumoniae (pneumococcus) exhibits a high degree of genomic diversity and plasticity. Isolates with high genomic similarity are grouped into lineages that undergo homologous recombination at variable rates. PMEN1 is a pandemic, multidrug-resistant lineage. Heterologous gene exchange between PMEN1 and non-PMEN1 isolates is directional, with extensive gene transfer from PMEN1 strains and only modest transfer into PMEN1 strains. Restriction-modification (R-M) systems can restrict horizontal gene transfer, yet most pneumococcal strains code for either the DpnI or DpnII R-M system and neither limits homologous recombination. Our comparative genomic analysis revealed that PMEN1 isolates code for DpnIII, a third R-M system syntenic to the other Dpn systems. Characterization of DpnIII demonstrated that the endonuclease cleaves unmethylated double-stranded DNA at the tetramer sequence 5′ GATC 3′, and the cognate methylase is a C5 cytosine-specific DNA methylase. We show that DpnIII decreases the frequency of recombination under in vitro conditions, such that the number of transformants is lower for strains transformed with unmethylated DNA than in those transformed with cognately methylated DNA. Furthermore, we have identified two PMEN1 isolates where the DpnIII endonuclease is disrupted, and phylogenetic work by Croucher and colleagues suggests that these strains have accumulated genomic differences at a higher rate than other PMEN1 strains. We propose that the R-M locus is a major determinant of genetic acquisition; the resident R-M system governs the extent of genome plasticity. IMPORTANCE Pneumococcus is one of the most important community-acquired bacterial pathogens. Pneumococcal strains can develop resistance to antibiotics and to serotype vaccines by acquiring genes from other strains or species. Thus, genomic plasticity is associated with strain adaptability and pneumococcal success. PMEN1 is a widespread and multidrug-resistant highly pathogenic pneumococcal lineage, which has evolved over the past century and displays a relatively stable genome. In this study, we characterize DpnIII, a restriction-modification (R-M) system that limits recombination. DpnIII is encountered in the PMEN1 lineage, where it replaces other R-M systems that do not decrease plasticity. Our hypothesis is that this genomic region, where different pneumococcal lineages code for variable R-M systems, plays a role in the fine-tuning of the extent of genomic plasticity. It is possible that well-adapted lineages such as PMEN1 have a mechanism to increase genomic stability, rather than foster genomic plasticity.